2018
DOI: 10.1002/vnl.21683
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the magnesium battery electrolyte properties through gamma irradiation of nano polymer electrolytes doped with magnesium oxide nanoparticles

Abstract: Nanocomposite polymer electrolytes (NCPE) were prepared using nano polyethylene oxide PEO doped with Magnesium (Mg) salts. Gamma irradiation was utilized to improve the PEO-Mg salts particle sizes. Consequently, Magnesium Oxide (MgO) nanoparticles were prepared by green synthesis and incorporated into PEO-Mg salts to improve their properties toward magnesium battery electrolyte applications. The prepared samples were examined before and after exposures to the radiation doses. Dynamic light scattering (DLS) ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…3, which includes mycotoxins that are not classified as carcinogenic to humans [ 42 ]. The toxicity of ZEN in vivo was studied by many research mostly reported the hazardous effect of Zearalenone on the reproductive systems either in male or female [ 42 ], also there was a specific concern about the lipid peroxidation of membranes which is included in the means by which ZEN exert its toxic action on human [413, another concern was the findings of [ 44 ] who demonstrated the ability of Zearalenone to disrupt liver functions and affect the liver thoroughly to the degree of suppression of cytochrome P450 in the liver results of our work gave clear data about the distribution of Zearalenone in different body organs which in turn could reveal the most susceptible organs that could suffer from Zearalenone/derivatives toxicity [ [121] , [122] , [123] , [124] , [125] , [126] , [127] , [128] , [129] , [130] , [131] , [132] , [133] , [134] , [135] , [136] , [137] , [138] , [139] , [140] , [141] , [142] , [143] , [144] , [145] ]. By examining the beneficial effect of L. plantarum on the organ exposure to Zearalenone/derivatives, results revealed that although the administration of L. plantarum did not significantly alter the accumulation of [ 125 I]-iodo-ZEN in different mice organs and there were observed similarity in the pattern of Zearalenone distribution through different organs yet there was marked reduction in the Zearalenone concentration in the ovary and that was observed from the 1st 5 min of administration, and since the ovaries are considered the most sensitive (target) organ of Zearalenone toxicity that could provide additional benefit for the use of LAB as it was reported to demonstrate anti-inflammatory, anti-genotoxic and improve ovarian fertility [ 45 ], the decline in the accumulation of [ 125 I]iodo ZEN in mice organs may be attributed to the lactic acid bacterial capability to bind and/or alter ZEN to other compound [ 9 ].…”
Section: Discussionmentioning
confidence: 84%
“…3, which includes mycotoxins that are not classified as carcinogenic to humans [ 42 ]. The toxicity of ZEN in vivo was studied by many research mostly reported the hazardous effect of Zearalenone on the reproductive systems either in male or female [ 42 ], also there was a specific concern about the lipid peroxidation of membranes which is included in the means by which ZEN exert its toxic action on human [413, another concern was the findings of [ 44 ] who demonstrated the ability of Zearalenone to disrupt liver functions and affect the liver thoroughly to the degree of suppression of cytochrome P450 in the liver results of our work gave clear data about the distribution of Zearalenone in different body organs which in turn could reveal the most susceptible organs that could suffer from Zearalenone/derivatives toxicity [ [121] , [122] , [123] , [124] , [125] , [126] , [127] , [128] , [129] , [130] , [131] , [132] , [133] , [134] , [135] , [136] , [137] , [138] , [139] , [140] , [141] , [142] , [143] , [144] , [145] ]. By examining the beneficial effect of L. plantarum on the organ exposure to Zearalenone/derivatives, results revealed that although the administration of L. plantarum did not significantly alter the accumulation of [ 125 I]-iodo-ZEN in different mice organs and there were observed similarity in the pattern of Zearalenone distribution through different organs yet there was marked reduction in the Zearalenone concentration in the ovary and that was observed from the 1st 5 min of administration, and since the ovaries are considered the most sensitive (target) organ of Zearalenone toxicity that could provide additional benefit for the use of LAB as it was reported to demonstrate anti-inflammatory, anti-genotoxic and improve ovarian fertility [ 45 ], the decline in the accumulation of [ 125 I]iodo ZEN in mice organs may be attributed to the lactic acid bacterial capability to bind and/or alter ZEN to other compound [ 9 ].…”
Section: Discussionmentioning
confidence: 84%
“…The variation of conductivity with temperature is given in Figure 9C. Figure depicts linear increase in conductivity with increase of temperature which obey's Arrhenius theory and is given by, 45 σ=σ0expEakT, where σ 0 corresponds to pre‐exponential factor, k indicates Boltzmann constant, T is absolute temperature, and E a indicates activation energy which is the energy gained by the ions to migrate between localized sites in polymer electrolytes 46 . E a is calculated by slope of linear fit of Figure 9C and is obtained to be 0.246 eV.…”
Section: Resultsmentioning
confidence: 99%
“…The radiotracer [ 125/131 I] iodobalsalazide is distributed rapidly in most organs at 5 min p.i. [27][28][29] The colon uptake was found to be 14% at 5 min p.i. and minimized to 32.90% at 24 h p.i.…”
Section: Molecular Modeling Studiesmentioning
confidence: 96%
“…On contrary, mesalamine showed active contribution toward binding of the parent compound balsalazide to PPARγ receptor, which is responsible for anticancer activity against colon cancer. [25][26][27][28][29][30] Although iodine-123 is the isotope of choice for medical imaging with a half-life to 13.22 h and decays by emission of gamma radiation with an energy of 159 keV.…”
Section: Introductionmentioning
confidence: 99%